New Spectrophotometric Methods for Estimation of Diosmin in Pharmaceutical Formulations Using Batch and FIA Systems: Abstract - Mohammed, Mayasa Mansour; Abed, Sadeem Subhi (Iraqi Journal of Science, 2021)
A new attempt is made to determine diosmin (DIO) in its pure form and in dietary supplements by using spectrophotometric flow injection analysis (FIA) assay method conjugated with batch method. The analysis was achieved depending on the oxidative coupling reaction with N, N-dimethyl-p-phenylenediamine (DMPD) to form a green dye which is measured at wavelength of 677 nm. The tested methods were found to be economical, delicate, precise and sturdy. The validation variables of the batch and FIA methods gave linearity in the determination range of DIO (1-35) μg/mL and (5-120) μg/mL demonstrated calibration graphs with linearity coefficient values of r2 =0.9989 and r2 =0.9991, respectively. Limits of quantitation (LOQ) values were found to be (0.8463 and 1.022) μg/mL, while limits of detection (LOD) were (0.2539 and 0.3067) µg/mL for the two methods, respectively. The precision for the developed methods denoted by relative standard deviation (RSD %), were 0.386 and 0.55 %, while the accuracy based on recovery values (Rec %) were 100.273 and 100.24, respectively. The relative error (RE %) was less than 1% for the batch method and (1.1%) for the FIA method. The values of these parameters were observed to fall within the speciﬁed accepted limits; therefore, the tested methods seem to be adequate for the analysis of DIO in pharmaceutical preparations.